2021
DOI: 10.1002/ppul.24939
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapies for treatment of resistant and refractory nontuberculous mycobacterial infections in patients with cystic fibrosis

Abstract: Respiratory infections caused by non‐tuberculous mycobacteria (NTM) are a major cause of morbidity for patients living with cystic fibrosis (CF), as NTM pulmonary disease (NTM‐PD) is challenging to both diagnose and eradicate. Despite the lengthy courses of the established regimens recommended by the Cystic Fibrosis Foundation (CFF) and European Cystic Fibrosis Society (ECFS) consensus guidelines, only about 50% to 60% of patients achieve culture conversion, and treatment regimens are often complicated by anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…Although less active against NTM compared with M. tuberculosis , bedaquiline has demonstrated in vitro bacteriostatic activity against MAC and M. abscessus . However, a real-world case series with a limited number of patients (n = 10) suggested that although it was able to improve symptoms and decrease bacterial load, sustained culture conversion after 6 months of treatment was not observed [ 96 ]. A Phase II/III trial to evaluate the efficacy and safety of treatment regimens containing bedaquiline in patients with refractory MAC-PD is currently underway (trial registration: NCT04630145).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although less active against NTM compared with M. tuberculosis , bedaquiline has demonstrated in vitro bacteriostatic activity against MAC and M. abscessus . However, a real-world case series with a limited number of patients (n = 10) suggested that although it was able to improve symptoms and decrease bacterial load, sustained culture conversion after 6 months of treatment was not observed [ 96 ]. A Phase II/III trial to evaluate the efficacy and safety of treatment regimens containing bedaquiline in patients with refractory MAC-PD is currently underway (trial registration: NCT04630145).…”
Section: Methodsmentioning
confidence: 99%
“…One example is tedizolid, an oxazolidinone typically used to treat acute bacterial skin and skin structure infections (ABSSSI), which has demonstrated efficacy in a macrophage model and in a case study of an immunocompromised patient with M. abscessus infection. Omadacycline, also more commonly used for ABSSSI, has similarly demonstrated significant in vitro activity against M. abscessus , but clinical data are currently limited to case series [ 96 , 97 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, Mtb strains resistant to some or all available antibiotics have emerged [ 5 , 6 ], including stains resistant to newly developed antibiotics such as bedaquiline, delamanid, and pretomanid [ 7 , 8 ], highlighting the need for novel treatment strategies for TB. Similarly, antibiotic resistance is of significant concern in infections caused by nontuberculous mycobacteria [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%